PENCEGAHAN DEMENSIA PADA LANSIA MELALUI TERAPI BILABONG DI BANJAR PUCAK SARI DENPASAR UTARA - Ni Luh Diah Pradnya Kerthiari; Ni Putu Juliadewi Eka Gunawati; Ni Luh Gede Padma Peratiwi; Putu Ayu Sani Utami (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
Background: The elderly are more vulnerable to health problems due to a decline in physiological, cognitive and brain function, especially in the case of dementia. One therapy that can to cope with dementia is a brain exercise that consists of an adaptation of local culture through collaberation between drama gong (Bilabong) and Balinese gamelan. Objective: To prevent the incidence of dementia in the elderly with